Double-blinded, placebo-controlled study of early tranexamic acid treatment in swine uncontrolled hemorrhage model. Issue 1 (January 2016) - Sondeen, Jill L.; Hanson, Margaret A.; Prince, Malcolm D.; de Guzman, Rodolfo; Polykratis, Irene A.; Aden, James K.; Cap, Andrew P.; Dubick, Michael A.
Abstract : BACKGROUND: Tranexamic acid (TXA) is an antifibrinolytic drug that was shown to increase survival in trauma patients, but the mechanisms remain unclear. The purpose of this double-blinded, randomized placebo-controlled study was to determine if TXA with hypotensive resuscitation with Hextend (HEX) or fresh frozen plasma (FFP) reduced blood loss (BL) and improved survival in a model of uncontrolled hemorrhage. METHODS: Instrumented, anesthetized pigs (n = 11 per group) were subjected to 24-mL/kg controlled hemorrhage, followed by transection of the spleen. After 15 minutes of bleeding, TXA (1.43 mg/kg/min) or normal saline (NS) was given over 10 minutes, and then 15-mL/kg HEX or FFP was administered. At 90 minutes, a second infusion of TXA or NS was given. BL, coagulation status, and 5-hour survival were determined. Tissue plasminogen activator (tPA) was added to blood samples collected before and after TXA administration to confirm that the TXA inhibited fibrinolysis. In addition, a comparison of a dose response to tPA-induced fibrinolysis was made between swine and human plasma in vitro. RESULTS: TXA prevented the rise in d-dimers that occurred after spleen injury. However, there was no significant effect of TXA on survival or BL compared with NS with HEX (HEX + NS, 17 ± 2 mL/kg vs. HEX + TXA, 17 ± 2 mL/kg) or FFP (FFP + NS, 7 ± 2 mL/kg vs. FFP + TXA, 12 ± 3 mL/kg), while FFP significantly reduced BL and increased survival compared with HEX in the NS-treated animals. The tPA-induced fibrinolysis was inhibited in the blood from TXA-treated animals, yet in fibrinolysis sensitivity studies, human plasma was 30 times more sensitive to tPA-induced fibrinolysis than swine plasma. CONCLUSION: TXA did not reduce BL, even though TXA was antifibrinolytic in the pigs. The possibility remains that the pig is highly resistant to fibrinolysis and not a good model to study the effects of antifibrinolytics or that fibrinolysis is not a major factor in bleeding from splenic injury. Abstract : Supplemental digital content is available in the text.